2022
DOI: 10.3390/foods11070996
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis of Staphylococcus aureus Reveals the Genes Involved in Survival at Low Temperature

Abstract: In food processing, the temperature is usually reduced to limit bacterial reproduction and maintain food safety. However, Staphylococcus aureus can adapt to low temperatures by controlling gene expression and protein activity, although its survival strategies normally vary between different strains. The present study investigated the molecular mechanisms of S. aureus with different survival strategies in response to low temperatures (4 °C). The survival curve showed that strain BA-26 was inactivated by 6.0 log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…The greA gene encodes a transcription elongation factor that affects bacterial gene transcription by regulating gene promoters, thereby regulating the environmental adaptation of bacteria [ 11 ]. In addition, the greA gene is recognized as a bacterial housekeeping gene, which, like the bacterial 16S ribosomal RNA, is an evolutionarily conserved transcription factor widely distributed in prokaryotes [ 12 ].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The greA gene encodes a transcription elongation factor that affects bacterial gene transcription by regulating gene promoters, thereby regulating the environmental adaptation of bacteria [ 11 ]. In addition, the greA gene is recognized as a bacterial housekeeping gene, which, like the bacterial 16S ribosomal RNA, is an evolutionarily conserved transcription factor widely distributed in prokaryotes [ 12 ].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Here, we demonstrated that KatA was involved in bacterial tolerance to oxidative stress and subsequent tolerance to fluoroquinolone antibiotics. Additionally, KatA affected the survival of S. aureus at low temperature (Masmoudi et al, 2010;Suo et al, 2022). PerR functions as a major repressed regulator of the response to H 2 O 2 in S. aureus, which replaces OxyR in many Gram-positive bacteria (Mongkolsuk and Helmann, 2002;Dubbs and Mongkolsuk, 2012).…”
Section: Discussionmentioning
confidence: 99%